Analisis Psikologi Sastra dalam Novel Hati Suhita Karya Khilma Anis - Yola, Sari; Rahayu, Sri (UIR Press, 2025)
Literary works are a reflection of life, and the psychology of society and personality are closely related. The purpose of this study is to characterize and examine the id, ego, and superego of the main character, which form the personality structure. The descriptive qualitative method used in this study produces data in the form of words and sentences that can be defined structurally using the theory of literary psychology. The data source used is the Novel Hati Suhita by Khilma Anis. The theory used in this study is Sigmund Freud's psychoanalytic theory. The techniques used in collecting this data are library research and hermeneutics, namely, the process of reading, documenting, and drawing conclusions. The results of the study showed that the Id appeared in Suhita's drive to be loved and recognized emotionally by her husband, in the character Suhita often kept it to herself without doing anything, harboring sadness and disappointment towards her husband's treatment. The ego emerged when Suhita managed her inner conflict by adjusting her desires to the reality of the household. The Ego aspect in the character Suhita is described when Suhita has dared to express her feelings of disappointment towards her husband and dared to leave her husband. The superego is seen from Suhita's decision to stay in marriage for the sake of moral values, family, and religion. This study shows that the id, ego, and superego shape Suhita's personality, which reflects the inner conflict between personal desires, social reality, and moral values.